2007
DOI: 10.1016/j.bbrc.2007.08.186
|View full text |Cite
|
Sign up to set email alerts
|

Bex1 knock out mice show altered skeletal muscle regeneration

Abstract: Bex1 and Calmodulin (CaM) are upregulated during skeletal muscle regeneration. We confirm this finding and demonstrate the novel finding that they interact in a calcium-dependent manner. To study the role of Bex1 and its interaction with CaM in skeletal muscle regeneration, we generated Bex1 knock out (Bex1-KO) mice. These mice appeared to develop normally and are fertile, but displayed a functional deficit in exercise performance compared to wild type (WT) mice. After intramuscular injection of cardiotoxin, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 30 publications
2
56
0
Order By: Relevance
“…The H19 lncRNA, up-regulated in Cul (Figure 5D), was also increased in SIRT1 mKO SCs induced to differentiate (Figure S5C). Of particular interest, transcripts typically expressed in either embryonic muscle and/or upregulated during muscle regeneration including the embryonic myosin heavy chain isoform ( Myh3 ), filamin C ( Flnc ), and brain expressed 1 ( Bex1 ) were increased in SIRT1 mKO SCs (Goetsch et al, 2005; Koo et al, 2007; Weydert et al, 1987, Table S2, see below Figure 7G). …”
Section: Resultsmentioning
confidence: 99%
“…The H19 lncRNA, up-regulated in Cul (Figure 5D), was also increased in SIRT1 mKO SCs induced to differentiate (Figure S5C). Of particular interest, transcripts typically expressed in either embryonic muscle and/or upregulated during muscle regeneration including the embryonic myosin heavy chain isoform ( Myh3 ), filamin C ( Flnc ), and brain expressed 1 ( Bex1 ) were increased in SIRT1 mKO SCs (Goetsch et al, 2005; Koo et al, 2007; Weydert et al, 1987, Table S2, see below Figure 7G). …”
Section: Resultsmentioning
confidence: 99%
“…The list of the differentially regulated genes (Fig 7E and Table S2) showed that a limited set of transcripts were either induced or repressed in the presence of GDF3. Several of the differentially regulated genes, including Bex1, (Jiang et al, 2016; Koo et al, 2007), Sgca (Matsumura et al, 1992) and Camk1g, have been implicated in muscle regeneration, muscle structure and/or Ca 2+ homeostasis, showing that macrophage derived GDF3 could elicit biologically relevant changes during muscle regeneration.…”
Section: Resultsmentioning
confidence: 99%
“…These transitional CM expressed genes involved in cellular growth (e.g., Tcea1 , encoding transcription elongation factor), CM differentiation ( Cbx3 an epigenetic silencer that promotes pluripotent cells differentiation; Casq2, calsequestrin 2; Ckm, creatinine kinase) and the metabolic switch from glycolysis (reduced Pgam1 expression) to fatty acid oxidation (increased Fabp3 , Fabp4 , encoding fatty acid binding protein; Fig 4C ) that characterizes mature CMs (Vander Heiden et al, 2010). Further maturation occurred by P21 when there was decreased expression of calmodulin-interacting proteins, Bex1 and Bex4, that promote muscle regeneration (Koo et al, 2007). …”
Section: Discussionmentioning
confidence: 99%